2022
DOI: 10.3390/md20020088
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Defense Gene Expression and the Resistance of Date Palm to Fusarium oxysporum f. sp. Albedinis in Response to Alginate Extracted from Bifurcaria bifurcata

Abstract: In many African countries, the Bayoud is a common disease spread involving the fungus Fusarium oxusporum f. sp. albedinis (Foa). The induction of plant natural defenses through the use of seaweed polysaccharides to help plants against pathogens is currently a biological and ecological approach that is gaining more and more importance. In the present study, we used alginate, a natural polysaccharide extracted from a brown algae Bifurcaria bifurcata, to activate date palm defenses, which involve phenylalanine am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
7
0
1
Order By: Relevance
“…Recientemente, Bouissil et al (2022) hicieron uso de este tipo de repositorios para organizar perfiles de expresión genética derivados de factores de inducción de proteínas de defensa y resistencia de la palmera datilera a Fusarium oxysporum f. sp. albedinis, en respuesta a alginato extraído de Bifurcaria bifurcata.…”
Section: Registro Y Gestión De Metadatos Complementarios Yunclassified
“…Recientemente, Bouissil et al (2022) hicieron uso de este tipo de repositorios para organizar perfiles de expresión genética derivados de factores de inducción de proteínas de defensa y resistencia de la palmera datilera a Fusarium oxysporum f. sp. albedinis, en respuesta a alginato extraído de Bifurcaria bifurcata.…”
Section: Registro Y Gestión De Metadatos Complementarios Yunclassified
“…This polysaccharide has been widely used in the food [ 5 ], pharmaceutical, biomedical [ 6 ], and industrial fields [ 7 ]. In addition, several studies have reported the use of alginate in agriculture to stimulate plant growth and development [ 8 , 9 ] and to induce plant resistance mechanisms [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated some functional mechanisms of oligoalginates in plants [ 25 , 26 ]. Recently, tomato seedlings and date palm roots treated with oligoalginates from Bifurcaria bifurcata showed the induction of natural defenses by increasing PAL activity and the production of polyphenols [ 11 , 12 ]. This has been accompanied by the induction of gene expression and resistance to Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayoud disease [1][2][3][4][5], caused by the telluric fungus pathogen Fusarium oxysporum f. sp. albedinis (F.o.a) [6][7][8][9], represents the leading dangerous agent of date palms cultivation, having killed more than 15 million Moroccan and Algerian date palm trees.…”
Section: Introductionmentioning
confidence: 99%